PERENCANAAN PAKET UMRAH PADA PT. PENJURU WISATA NEGERI DI PEKANBARU - Suci Ramadhani Syafitri; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Making an Umrah package requires planning, this planning involves calculations, considerations and estimates. In preparing an Umrah package plan, an interesting object must be selected as an attraction to encourage buyers of the Umrah package. This study aims to determine the stages of Umrah package planning at PT. Penjuru Wisata Negeri in Pekanbaru. From this research it can be seen that the planning factors carried out by PT. Penjuru Wisata Negeri are the purpose of the trip, prepared destinations, length of stay, costumer budget, accomodataion desired, travel documents. This study uses a qualitative method with a descriptive approach to describe and display the existing conditions at a research site by collecting data and information obtained directly from the field. The key informants in this study are Operational Managers, Branch Managers, Administrative Staff. Data collection techniques used are literature studies, interviews, observation, and documentation. Based on the research results, it can be concluded that planning factors are still an obstacle for PT. Penjuru Wisata Negeri is a costumer budget factor. This is due to differences in accommodation and transportation rates after the Covid-19 pandemic. Keywords: planning, umrah packages, travel.